2020
DOI: 10.3390/ijerph17228499
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Time-Domain and Frequency-Domain Heart Rate Variability Measures of Fatigued Drivers

Abstract: The effects of fatigue on a driver’s autonomic nervous system (ANS) were investigated through heart rate variability (HRV) measures considering the difference of sex. Electrocardiogram (ECG) data from 18 drivers were recorded during a simulator-based driving experiment. Thirteen short-term HRV measures were extracted through time-domain and frequency-domain methods. First, differences in HRV measures related to mental state (alert or fatigued) were analyzed in all subjects. Then, sex-specific changes between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…The SDNN changed little after tPCS intervention, and there was no significant difference before and after intervention. However, the findings of Zeng et al [ 51 ] differed from those of our study. That study showed that the occurrence of fatigue will increase the SDNN value in driving tasks.…”
Section: Discussioncontrasting
confidence: 99%
“…The SDNN changed little after tPCS intervention, and there was no significant difference before and after intervention. However, the findings of Zeng et al [ 51 ] differed from those of our study. That study showed that the occurrence of fatigue will increase the SDNN value in driving tasks.…”
Section: Discussioncontrasting
confidence: 99%
“…The studies included in this review have measured cardiovascular parameters using different types of sensors. Electrode-based ECG has been the most frequently used data collection hardware for HR and HRV data [ 21 , 30 , 52 , 54 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. HR and HRV analysis typically requires three leads in the ECG to detect the R peak in the QRS complex [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Post-hoc pairwise comparison between two measures or two groups of participants have been employed by several studies for further analysis [ 56 , 64 , 71 , 72 , 76 ]. Some of the other statistical analysis methodologies used are Pearson correlation [ 59 ], parametric analysis with T-scores [ 68 ], Mann-Whitney U tests [ 66 ], and log-likelihood [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress responses are observed amid the contrasting actions of the sympathetic nervous system (SNS) and parasympathetic nervous system (PNS), which form the ANS. HRV reflects the related activity level [23] and is an index of the time-varying differences between two adjacent heartbeats that have been used for the objective evaluation of mental health and stress [24]. Figure 1 describes stress-induced physiological, psychological, and behavioral reactions manifested by SNS and PNS interactions with ANS stimulation.…”
Section: Stress and Heart Rate Variabilitymentioning
confidence: 99%